2020
DOI: 10.1111/are.14845
|View full text |Cite
|
Sign up to set email alerts
|

Optimal dietary lysine improves growth performance, increases protein deposition and reduces lipid accumulation in tambaqui ( Colossoma macropomum ) juveniles

Abstract: The present study aimed to determine the dietary lysine requirement for tambaqui (Colossoma macropomum) juveniles, based on growth performance, whole‐body composition, haematological parameters and plasma metabolites. For that purpose, an 81‐day feeding trial was conducted with 150 tambaquis distributed in 15 aquariums (300 L) in a completely randomized design, with five treatments and three replicates. Five diets were formulated and crystalline l‐lysine was added to obtain diets with lysine concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 53 publications
1
2
0
2
Order By: Relevance
“…In mammals, appropriate lysine supplementation in feed can promote growth, increase the content of carnitine, and reduce triglyceride levels in tissues [13]. Previous studies in fish also found that optimal dietary lysine could reduce lipid accumulation in some fish species, including tambaqui (Colossoma macropomum) [54] and Nile tilapia [55]. These findings agree with our findings in juvenile largemouth bass.…”
Section: Akt/foxo1supporting
confidence: 91%
“…In mammals, appropriate lysine supplementation in feed can promote growth, increase the content of carnitine, and reduce triglyceride levels in tissues [13]. Previous studies in fish also found that optimal dietary lysine could reduce lipid accumulation in some fish species, including tambaqui (Colossoma macropomum) [54] and Nile tilapia [55]. These findings agree with our findings in juvenile largemouth bass.…”
Section: Akt/foxo1supporting
confidence: 91%
“…Thr) can reduce body protein synthesis, favouring fat deposition through amino acid catabolism (Abimorad et al, 2010), which would increase the excretion of nitrogenous compounds in water. Therefore, the whole‐body composition is critical in evaluating the quality of fish carcasses (Teixeira et al, 2020). However, the best body crude protein and ash contents were in fish that received intermediate levels of Thr in the diet (9.40–11.20 g/kg), a phenomenon that may be associated with the accretion of nutrients in the fish body (Ahmad et al, 2021; Nguyen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many studies with species of interest to pisciculture have sought to determine the nutritional requirement of essential amino acids as a strategy to formulate more efficient feeds for fish (Ahmed & Ahmad, 2021; Ahmad et al, 2021; Bomfim et al, 2020; Khan et al, 2020; Marchao et al, 2020; Silva Liebl et al, 2022; Teixeira et al, 2020). Amino acids are essential polypeptides utilized by the fish to improve the growth and synthesis of protein and bioactive molecules, contributing to fish metabolism and health (Nie et al, 2018; Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A suplementação de lisina em dietas deficientes deste aminoácido para peixes, proporciona aumento no ganho de peso, melhora da conversão alimentar, redução de gordura na carcaça e maior retenção de nitrogênio (MARCHÃO et al, 2020;TEIXEIRA et al, 2020). Em contrapartida, sua deficiência na dieta ocasiona impacto negativo no desempenho de peixes, devido a limitação de síntese proteica (FURUYA et al, 2004;NRC, 2011).…”
Section: Lisina Na Nutrição De Peixesunclassified